Effects of Standardized Ileal Digestible Lysine:Crude Protein Ratio in Diets with or without Distillers Dried Grains with Solubles on Growth Performance of 25 to 45 lb Pigs - Jessica L. Smallfield; Mike D. Tokach; Katelyn N. Gaffield; Robert D. Goodband; Joel M. DeRouchey; Jason C. Woodworth; Jordan T. Gebhardt; Henrique S. Cemin; Melissa R. Pietig; Zach A. Schumacher; Jose A. Soto (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 5,059 pigs (PIC 800 × Camborough and DNA 600 × 241; initially 24.3 ± 1.99 lb) were used in an 18-d trial to evaluate SID Lys:CP ratios for 25 to 45 lb pigs in diets with and without DDGS, resulting in diets that contained high or low levels of SBM on growth performance. Pigs were weaned at approximately 21 d of age and housed in mixed-sex pens with approximately 35 pigs per pen. A pelleted early nursery diet was fed to all pigs from weaning until the beginning of the experiment. When pigs reached approximately 24 lb, pens were assigned to one of 12 treatments in a completely randomized design with pen serving as the experimental unit. A total of 143 pens were used, resulting in 11 or 12 replications per dietary treatment. Experimental treatments were arranged in a 2 × 6 factorial with main effects of DDGS (0 or 15%) and SID Lys:CP ratio (6.01, 6.22, 6.45, 6.70, 6.97, or 7.26). Pigs were weighed at the beginning and at the end of the study on d 18. Overall (d 0 to 18), a SID Lys:CP × DDGS interaction was observed (linear, P < 0.001) for feed efficiency where increasing SID Lys:CP ratio in diets without DDGS improved (P < 0.001) F/G quadratically, with the poorest F/G on the lowest and highest SID Lys:CP ratios; whereas in the diets with DDGS, F/G worsened (quadratic, P < 0.002) as the SID Lys:CP ratio increased above 6.45. For the main effects, ADG increased quadratically (P = 0.021) as the SID Lys:CP ratio increased, with the greatest ADG with ratios of 6.45 to 6.97. Conversely, ADFI increased linearly (P = 0.018) as SID Lys:CP increased up to the highest level tested. A tendency was observed for pigs fed no DDGS resulting in increased (P = 0.071) ADG and improved (P = 0.010) F/G. In conclusion, formulating diets to the SID Lys:CP ratio of 6.70 without DDGS and 6.45 in diets with DDGS improves feed efficiency. Further increasing the ratio leads to a reduction in feed efficiency, possibly due to nitrogen becoming the limiting factor as crude protein is decreased. Additionally, feeding diets without DDGS can lead to an improvement in ADG and F/G.
Keywords: crude protein; distillers dried grains with solubles; lysine; nursery pig; SID Lys:CP